ANALISIS AKUNTABILITAS PELAYANAN KANTOR LURAH BUKIT TIMAH KECAMATAN DUMAI SELATAN KOTA DUMAI DALAM PELAKSANAAN PELAYANAN ADMINISTRASI KEPENDUDUKAN - Erlianti, Dila (Jurnal Niara, 2019)
Kelurahan as the lowest administrative government unit in the process of implementing services that come into direct contact with the community is very important in implementing service principles, both institutions that carry out services and target groups that receive administrative services in the kelurahan. The purpose of this study is to see transparency, accountability, conditional, participatory, equal rights, balance of rights and obligations and factors that influence population administration services. The research method used with a quantitative approach with a sample population with questionnaire techniques and interviews with data analysis using descriptive statistics and scale of data measurement using a rating scale. The results of the research show that the service is good enough and is influenced by participatory and equal rights in a service process as well as the factors that hinder the lack of transparency and accountability in the implementation of services.